Is Inflation Targeting Still on Target? The Recent Experience of Latin America - Luis Felipe Cespedes; Roberto Chang; Andres Velasco (Inter-American Development Bank (IDB), 2013)
This paper reviews the recent experience of a half-dozen Latin American inflation targeting (IT) nations. Repeated and large deviations from the standard IT framework are documented: exchange market interventions have been lasting and widespread; the real exchange rate has often become a target of policy, though this target is seldom made explicit; a range of other non-conventional policy tools, especially changes in reserve requirements but occasionally taxes or restrictions on international capital movements, also came into common use. As in developed nations, during the 2008-2009 crisis issues of liquidity provision took center stage. A first evaluation of the emerging modified framework of monetary policy is also attempted. In general terms, the new approach seems to have been effective, at the very least since the region weathered the crisis reasonably well. But also, and perhaps more importantly, many questions remain about the desirability of non-conventional monetary policies in Latin America.
Keywords: E52; E58; F41; 330